THEORETICAL APPROACHES TO THE CREATION OF DYNAMIC MAPS ENVIRONMENTAL PROBLEMS OF UKRAINE - Дудун, Тетяна; Лисенко, Анна (SWorldJournal, 2022)
Urgent environmental problems that are characteristic of the territory of Ukraine are highlighted. The theoretical aspects of ecological cartography were highlighted, a review of special terminology and the history of the emergence of this direction in ca